Harnessing Canva infographics to enhance engagement in online learning - Azudin, Ahmad Rashidi; Mazeni, Noor Azizah; Idris, Nur Azimah; Samsudin, Norshuhada; Libasin, Zuraira (Universiti Teknologi MARA, Pulau Pinang, 2025)
The rapid shift toward online learning has intensified the challenge of sustaining student engagement and ensuring meaningful comprehension. Traditional lecture slides and text-heavy resources often fail to capture learners’ attention, resulting in reduced motivation and cognitive overload. Visual learning strategies, particularly infographics, have shown promise in simplifying complex concepts and supporting retention. This study explores the integration of Canva-designed infographics into higher education online courses. Infographics were developed to represent key course concepts and shared with students through learning management systems and synchronous online lectures. Informal feedback and instructor observations indicated that the visuals enhanced clarity, improved recall, and increased participation during discussions. Students reported that Canva-based infographics made learning materials more engaging and easier to understand compared to conventional slides. While challenges such as design time and balancing visual appeal with accuracy were noted, the findings suggest that Canva provides educators with an accessible tool to foster engagement in digital classrooms. Future work should employ systematic evaluations, such as pre- and post-tests or large-scale surveys, to measure the direct impact on learning outcomes.